2019
DOI: 10.26502/jbsb.5107004
|View full text |Cite
|
Sign up to set email alerts
|

Study of Water Pollutants in El-Mahmoudia Agricultural Irrigation Stream at El-Beheira Governorate, Egypt

Abstract: Background: Diverse types of agricultural, domestic, industrial, and municipal pollutants are discarded in agricultural water streams. These contaminants affect water quality extensively, therefore, current study aimed to scrutinize types of water pollutants in El-Mahmoudia water canal during winter, spring, summer, and autumn seasons.Materials and Methods: Organic pollutants and pesticide residues were analyzed using the gas-chromatographymass spectrometry (GC-MS). Heavy metals were determined by the atomic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The variation of pesticide levels between the current soil samples may be returned to many factors that play an important role in the persistence and degradation of pesticides in the soil such as soil characteristics and soil environmental factors [39]. Also, levels of pesticides in soil depend on their levels in irrigation water as reported by many Egyptian studies who noticed that levels of pesticides in River Nile water varied according to the type of irrigation water and level of water pollution [40][41][42][43].…”
Section: Pesticide Residues In Soil Samplesmentioning
confidence: 99%
“…The variation of pesticide levels between the current soil samples may be returned to many factors that play an important role in the persistence and degradation of pesticides in the soil such as soil characteristics and soil environmental factors [39]. Also, levels of pesticides in soil depend on their levels in irrigation water as reported by many Egyptian studies who noticed that levels of pesticides in River Nile water varied according to the type of irrigation water and level of water pollution [40][41][42][43].…”
Section: Pesticide Residues In Soil Samplesmentioning
confidence: 99%
“…El‐Mahmoudia canal water quality conditions were investigated in some publications. Radwan et al (2019) reported that a significant deterioration of physical, chemical, and heavy metals pollutants, due to agricultural and domestic effluents was noticed. For biological conditions of the canal, Kheirallah (2015) stated that the water course from south to north has an increase in biological pollutants.…”
Section: Introductionmentioning
confidence: 99%